Epidemiological Patterns of Preterm and Very Low Birth Weight Deliveries: A Decade-Long Multi-Center Study Across Selected Tertiary Obstetric Centers in Pakistan - Shakeel, Fauzia; Kenjher, Kenjher; Khan, Sumeira Naeem; Abid, Tahira; Shams, Amber; Hamza, Sarbissa (Journal of Neonatal Surgery, 2025)
Background: Preterm birth and very low birth weight (VLBW) are leading causes of neonatal morbidity and mortality worldwide, with the highest burden in low- and middle-income countries (LMICs). Despite notable progress in maternal and neonatal health, Pakistan continues to record high rates of preterm delivery and neonatal death. This study aimed to analyze epidemiological trends, maternal determinants, and neonatal outcomes associated with preterm and VLBW deliveries across selected tertiary obstetric centers in Pakistan over a ten-year period. Methods: A retrospective multi-center cohort study was conducted across selected tertiary obstetric hospitals in Pakistan from January 2013 to December 2023. Data from delivery registers and neonatal records were reviewed for all live births between 24 and 37 weeks of gestation. Maternal demographic, obstetric, and clinical characteristics were analyzed alongside neonatal outcomes. Statistical analyses were performed using SPSS v26. Trends were examined over time, and multivariate logistic regression identified predictors of preterm and VLBW births. Results: Among 89,612 live births, 9,746 (10.8%) were preterm and 3,214 (3.6%) were VLBW. The prevalence of preterm birth rose from 9.1% in 2013 to 12.2% in 2023 (p < 0.001). Major determinants included maternal age < 20 years (aOR 1.72, 95% CI 1.43–2.06), grand multiparity (aOR 1.51, 95% CI 1.29–1.77), inadequate antenatal care (aOR 1.89, 95% CI 1.64–2.21), hypertensive disorders (aOR 2.32, 95% CI 1.98–2.72), multiple gestation (aOR 3.14, 95% CI 2.65–3.74), and maternal infections (aOR 1.67, 95% CI 1.34–2.08). Neonatal mortality among VLBW infants declined modestly from 36.4% to 28.2% but remained high overall. Respiratory distress, sepsis, and prematurity complications accounted for most deaths. Conclusions: Preterm and VLBW deliveries remain a major public-health challenge in Pakistan. Rising incidence and persistently high neonatal mortality reflect systemic gaps in antenatal care, infection control, and neonatal intensive-care capacity. Strengthening preventive strategies, improving antenatal surveillance, and expanding NICU infrastructure are essential to achieve sustainable neonatal-survival goals in LMIC settings.